Brines in deep horizons of the Udachnaya kimberlite pipe - S. V. Alekseev; L. P. Alekseeva; A. S. Gladkov; N. S. Trifonov; E. V. Serebryakov; S. S. Pavlov; A. V. Il’in (Геодинамика и тектонофизика)
The study was focused on groundwaters sampled from boreholes drilled to deep horizons of the Udachnaya kimberlite pipe and the host sedimentary strata. Brines in the rocks significantly complicate underground mining. Analysis of the hydrogeological setting is required to ensure safety during mining to the design levels. The features of chemical composition and the geochemical evolution of brines in the crust can be clarified in a more detail on the basis of new reliable data on strong chloride saline solutions that formed in complex geological and tectonic conditions. Kimberlite and water samples were taken from the ore bodies and host sedimentary strata at the depth of 680–980 m. Conventional methods of quantitative and instrumental analysis were applied to study the chemical composition of brines. Mineral composition of kimberlite was determined by powder diffractography and X-ray fluorescence methods. Geological, structural and tectonophysical methods were used to reveal and describe the tectonic structure of the kimberlite pipe area. Groundwaters with salinity of 280–406 g/L are strong and very strong calcium chloride brines. The chlorine-bromine ratio has a small range of 48–57; the sodium-chlorine ratio varies from 0.11 to 0.18. According to their geochemical features, the studied groundwaters are metamorphosed brines that have analogues across the Siberian platform. Physical and chemical processes were simulated to investigate the degrees of saturation of strong brines relative to the minerals of water-bearing rocks. The simulation results show that the brines in the Western ore body of the Udachnaya pipe are strongly undersaturated in the deep horizons in comparison to carbonate, sulfate and chloride minerals. This suggests possible dilution of brines during their geochemical evolution. A detailed study of the tectonic structure identified structural elements that control the distribution and migration of groundwaters in the rocks. In the mining sites, brines occur mainly in the fault zones, fault junctions and intersections with the contacts of kimberlite bodies. Integration of hydrogeological and geostructural data can provide a basis for prediction and assessment of the sites with increased water inflow in the deep horizons involved in mining.